PERAN BUDAYA ORGANISASI TERHADAP IMPLEMENTASI NEW PUBLIC MANAGEMENT DALAM PENINGKATAN KINERJA MANAJERIAL SEKTOR PUBLIK - Lili Indrawati (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2017)
Abstract: The purpose of this research is to analyze and prove the role of organization cultures, against implementation of new public management in enhancing public sector managerial performance. The research was carried out at the Cimahi local government.  The number of respondent was 258 employees from 42 working units.  The research method used is purposive sampling. To analyze the data from the respondent is interaction regression.  The research shows that organizational culture does not affect the relationship between NPM and public sector managerial performanceKeywords: New Public Management, Organizational Culture, Leadership Style, Intellectual Capital and Performance of Public Sector Managerial, Cimahi Local Government